Successful Diagnostic Stewardship for Clostridioides difficile Testing in Pediatrics. (October 2020) - Halabi, Katia; Saiman, Lisa; Zachariah, Philip; Acker, Karen; Cannon, Jean-Marie; Messina, Maria; Mangino, Diane; Balzer, Krystal; Green, Daniel; Salvatore, Christine
Abstract : Background: As many as 40% of infants aged ≤12 months and 10%–28% of children aged 13–24 months are colonized by Clostridioides difficile. The IDSA and the SHEA recommend that testing should never be routinely recommended for infants ≤12 months of age and should not be routinely performed for children 1–2 years of age unless other causes are excluded. We report implementation of C. difficile diagnostic stewardship at 2 children's hospitals. Methods: We implemented age-based restrictions for C. difficile testing at hospital A (∼200-bed, free-standing, children's hospital) and hospital B (∼100-bed children's hospital within a larger hospital). Both sites are part of the same multicampus institution, and both used nucleic acid amplification testing to detect C. difficile throughout the study. In May 2018, we implemented an electronic order set for C. difficile that provided alerts to avoid testing young infants and patients with recent use of laxatives, stool softeners, or enemas, but providers could order C. difficile testing at their discretion. In October 2018, we implemented a more restrictive diagnostic stewardship algorithm for C. difficile. No testing was allowed for infants aged ≤12 months. Approval pediatric infectious diseases staff was required to test children aged 13–24 months. Pathology resident approval was required to test children aged ≥24 months who had received laxatives, stool softeners, or enemas within ≤24 hours. Clinical microbiology laboratory supervisors reinforced rejection of nondiarrheal stool specimens for testing. Providers at both campuses were informed about the new testing guidelines by e-mail. We compared the number of tests sent and positive cases of healthcare facility-onset C. difficile (HO-CDI) by age strata before and after the implementation of the restrictive testing algorithm. Results: After the intervention, the number of tests in infants significantly declined; 2 infants aged ≤12 months and 4 infants aged 13–24 months were tested for C. difficile (Table). After the intervention, the number of tests per month declined at hospital A, as did the number of HO-CDI cases at both hospitals. Rejections of nondiarrheal stools significantly increased after the intervention ( P < .001). Conclusions: C. difficile diagnostic stewardship for children was successfully implemented using a rule-based alert system in the electronic health record. This intervention was associated with a reduced number of tests sent and cases of HO-CDI. This strategy was cost-saving and prevented misdiagnosis, unnecessary antibiotic therapy, and overestimation of HO-CDI rates. Funding: None Disclosures: None